Pharmaceutical Botany. Manual for the Unified State Qualification Examination (USQE), Stage 1. the “Krok-1” Integrated Test-Based Exam and the English Language Proficiency Test Preparation for the Second and Third-Year Students of the Pharmaceutical Faculties, Specialty 226 “Pharmacy, Industrial Pharmacy”, Specialization “Technology of Perfumes and Cosmetics”. Part II - Корнієвський, Юрій Іванович; Корнієвська, Валентина Григорівна; Куліченко, Алла Костянтинівна; Панченко, Світлана Валеріївна; Мазулін, Георгій Владиленович; Korniievskyi, Yu. I.; Korniievska, V. H.; Kulichenko, A. K.; Panchenko, S. V.; Mazulin, H. V. (Запорізький державний медичний університет, 2021)
The manual aims to prepare pharmaceutical students for the Unified State Qualification Examination (USQE), Stage 1 that consists of the following parts: the “Krok-1” Integrated Test-Based Exam and the English Language Proficiency Test.